A systematic review of screening tools in non-young children and adults for autism spectrum disorder. (September 2018) - Hirota, Tomoya; So, Ryuhei; Kim, Young Shin; Leventhal, Bennett; Epstein, Richard A.
Abstract: Background: Existing reviews of screening tools for Autism Spectrum Disorder (ASD) focus on young children, and not all screening tools have been examined against validated diagnostic procedures. Aims: To examine the validity of screening tools for ASD in non-young children and adults to provide clinical recommendations about the use of these tools in a variety of clinical settings. Methods and Procedures: Electronic databases, including MEDLINE, EMBASE, PsychINFO, Cochrane Library and CINAHL, were searched through March 2017. Studies examining the validity of ASD screening tools against the Autism Diagnostic Observation Schedule and/or the Autism Diagnostic Interview - Revised in non-young children (age 4 or above) and adults were included. Three authors independently reviewed each article for data extraction and quality assessment. Outcomes and Results: 14 studies met the inclusion criteria, of which 11 studies were with children (4–18 years of age) and 3 studies included adults only (19 years of age and above). Included studies were conducted in a general population/low-risk sample (N = 3) and a clinically referred/high-risk sample (N = 11). In total 11 tools were included. Conclusions and Implications: Only three screening tools (the Autism-Spectrum Quotient, the Social Communication Questionnaire, and the Social Responsiveness Scale) were examined in more than 2 studies. These tools may assist in differentiating ASD from other neurodevelopmental and psychiatric disorders or typically developed children. In young adult populations, the paucity of the existing research in this group limits definitive conclusion and recommendations.